2016
DOI: 10.1007/s00405-016-4244-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of narrow-band imaging (NBI) endoscopy in optical biopsy of vocal cord leukoplakia

Abstract: The aim of this study was to investigate whether observing microvascular changes by narrow-band imaging (NBI) endoscopy in the area surrounding leukoplakia is sufficient for discriminating between benign and malignant patterns of vocal cord leukoplakia. A total of 282 patients were investigated using white-light high-definition TV laryngoscopy and NBI endoscopy from 6/2013 to 8/2015, and 63 patients with a primary case of laryngeal leukoplakia were enrolled. Patients were divided into two groups based on leuko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 20 publications
0
54
0
1
Order By: Relevance
“…One set of data was collected for analysis, in which Ni type V was considered test positive, and another set of data in which Ni type IV as well as Ni type V were considered test positive. This procedure was chosen to assess the diagnostic accuracy of the Ni classification when only Ni type V was considered test positive, as previously recommended, compared to the diagnostic accuracy when Ni type IV was also considered test positive inspired by the ELS and the recently recommended focus on perpendicular vascular changes . We used the terms neoplasia to cover the entire histopathological range of neoplasia from light, moderate, and severe dysplasia to carcinoma in situ and cancer (lesions with malignant potential) and non‐neoplasia for all other lesions, such as keratosis and inflammatory disease.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One set of data was collected for analysis, in which Ni type V was considered test positive, and another set of data in which Ni type IV as well as Ni type V were considered test positive. This procedure was chosen to assess the diagnostic accuracy of the Ni classification when only Ni type V was considered test positive, as previously recommended, compared to the diagnostic accuracy when Ni type IV was also considered test positive inspired by the ELS and the recently recommended focus on perpendicular vascular changes . We used the terms neoplasia to cover the entire histopathological range of neoplasia from light, moderate, and severe dysplasia to carcinoma in situ and cancer (lesions with malignant potential) and non‐neoplasia for all other lesions, such as keratosis and inflammatory disease.…”
Section: Methodsmentioning
confidence: 99%
“…The i‐SCAN image processing includes three algorithms for surface, contrast, and tone enhancement, providing visual enhancement and accentuating mucosal surface and vascular structures . All of these systems provide excellent images, and the access to such images in very high resolution has led to the invention of the term “optical biopsy.” Furthermore, all of these enhancement techniques can be applied to rigid or flexible video endoscopes in an office‐based setting or in the operating room. An awake patient usually needs local anesthetics to allow the scope sufficiently close to the mucosal lesion for evaluation of the vasculature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Stanikowa et al [17] the correlation between inappropriate vessel pattern around laryngeal leukoplakia and histological examination are consistent in 88.89% of cases. In our study, the vessel pattern in NBI had a good correlation with final histology and confirmed the findings of others [17]. We described and recommended the use of NBI endoscopy for the assessment of edges of the white plaque and surrounding mucosa to choose the appropriate treatment.…”
Section: Discussionmentioning
confidence: 85%
“…However, the findings of these studies on the NBI endoscopic diagnosis of vocal cord leukoplakia show a poor consistency. Staníková et al reported that the sensitivity of the diagnosis of malignant lesions in patients with vocal cord leukoplakia under the NBI endoscope was 88.0% and specificity was 89.5% . Yang et al carried out a differential diagnosis of suspicious malignant vocal cord lesions (including vocal cord leukoplakia) using the NBI endoscopy, according to which the sensitivity, specificity, PPV, NPV, and accuracy were 66.7%, 72.5%, 60.9%, 78.0%, and 70.6%, respectively .…”
Section: Discussionmentioning
confidence: 99%